Case Report: Reduced CSF Orexin Levels in a Patient With Sepsis - Ogawa, Yasuhiro; Ezaki, Seioh; Shimojo, Nobutake; Kawano, Satoru (Frontiers in Neuroscience, 2021)
Sepsis is a potentially lethal condition characterized by systemic inflammation and multiple organ failure, and sepsis-associated encephalopathy (SAE) is an independent risk factor for mortality in patients with sepsis. We previously reported that orexin improved survival in an animal model of sepsis by acting in the brain. Peripherally administered orexin entered the brain under the conditions of systemic inflammation because of BBB dysfunction and produced survival-related effects. As a therapeutic concept, we hypothesized that orexin treatment enhances recovery from sepsis by restoring reduced orexin levels in cerebrospinal fluid (CSF). Here, we report that CSF orexin levels were reduced in a 63-year-old woman with sepsis. The patient presented with coma, fever, headache, vomiting, and seizures upon arrival at the emergency room. She had a history of subarachnoid hemorrhage which led to the development of hydrocephalus, and as a consequence, a ventriculoperitoneal shunt (VP shunt) tube had been installed to ameliorate the complication. Physical examinations showed dehydration and abnormality of circulation, arterial blood gas analysis showed insufficient oxygenation, blood tests showed an inflammatory response, liver injury, kidney injury, hyperkalemia, and hyperglycemia, and radiographical examinations showed mild hydrocephalus and several old microinfarctions. She was diagnosed with sepsis because her Sequential Organ Failure Assessment (SOFA) score was 13 and Enterococcus faecalis was isolated form her blood and CSF. Status epilepticus, hyperglycemia, and sepsis-associated encephalopathy were considered possible causes of coma. Her CSF could be safely sampled because she had a VP shunt, although it is ethically difficult to sample CSF routinely from patients with sepsis. Reduced CSF orexin levels gradually recovered as she recovered from sepsis. Unexpectedly, orexin was detected in the blood, which is unusual in healthy humans. Blood orexin was not detected after recovery from sepsis. This result may imply that orexin leaks into the blood because of BBB dysfunction. To the best of our knowledge, this is the first report investigating orexin levels in the CSF and blood of a patient with sepsis, and the data obtained from this case may provide a new understanding of the pathophysiology of SAE.